SKRINING STATUS GIZI DAN SOSIALISASI PENTINGNYA KONSUMSI SUSU KEDELAI KURMA SEBAGAI MAKANAN KAYA ANTIOKSIDAN: Susu Kedelai Kurma Sebagai Makanan Kaya Antioksidan - Handayani, Yuni (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2025)
Nutritional status measures a person's condition that can be directly assessed through anthropometry, clinical, biochemical, and biophysical evaluations. Adolescent nutritional status can be evaluated through anthropometry, specifically by measuring Body Mass Index (BMI) by calculating Body Weight and Height, which are reliable indicators for measuring body fat in children and adolescents. This activity aims to assess nutritional status through screening and raise awareness about the importance of consuming date soy milk as an antioxidant-rich food. The target of this activity is adolescent girls at SMK dr. Soebandi. The methods used in this program include: (1) Nutritional status screening, starting with measurements of Body Weight, Height, and Upper Arm Circumference. (2) Providing information and education on balanced nutrition and anemia prevention. (3) Offering guidance on how to prepare date soy milk independently. (4) Distributing date soy milk to adolescent girls, with one bottle (250 ml) to be consumed daily for 7 days to prevent anemia. The adolescents were very enthusiastic and actively participated in the activities, receiving valuable information and education from the nutritional status screening results. Adolescents with suboptimal nutritional status will receive nutritional counseling, monitoring, and consultations with expert teams.